2018
DOI: 10.1007/s00125-018-4674-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary manganese and type 2 diabetes mellitus: two prospective cohort studies in China

Abstract: Dietary Mn was inversely associated with type 2 diabetes independently of TAC. In addition, this association was stronger in a high- rather than low-TAC diet. Plasma Mn and oxidative stress were mediators in the association between dietary Mn and type 2 diabetes. Future studies on absolute Mn intake should be conducted to study the potential non-linearity and optimal levels of dietary Mn and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 46 publications
(55 reference statements)
3
23
0
1
Order By: Relevance
“…Does BA-dependent regulation of Mn homeostasis have any impact on cardiometabolic disease? Some researchers have reported that patients with type 2 diabetes have plasma or serum Mn at levels higher than controls, whereas others have reported the opposite (73)(74)(75)(76). Because Mn levels must be maintained within a small range (31,44), it makes sense that both deficiency and excess of Mn would lead to negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Does BA-dependent regulation of Mn homeostasis have any impact on cardiometabolic disease? Some researchers have reported that patients with type 2 diabetes have plasma or serum Mn at levels higher than controls, whereas others have reported the opposite (73)(74)(75)(76). Because Mn levels must be maintained within a small range (31,44), it makes sense that both deficiency and excess of Mn would lead to negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Does BA-dependent regulation of Mn homeostasis have any impact on cardiometabolic disease? Some researchers have reported that patients with type-2 diabetes have plasma or serum Mn at levels higher than controls, while others have reported the opposite (73)(74)(75)(76). Because Mn levels must be maintained within a small range (31,44), it makes sense that both deficiency and excess of Mn would lead to negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Mn participates in various mechanisms involved in the genesis of DR, like the generation of ROS by having prooxidative properties and antioxidant mechanisms [127], and it could have a role in inflammation. In fact, the dietary intake of this micronutrient was inversely associated with the incidence of T2DM and was partially associated with lower OS measured by 8-hydroxydeoxyguanosine [128]; nevertheless, in preclinical studies, both deficient or excessive intake of Mn aggravated apoptosis by upregulating capase-3, caspase-8, and caspase-9 and inhibited Nrf2 signaling, while optimal intake protected against ROS, MDA, and protein carbonyl [129]. Mn may have a protective role against endothelial dysfunction by upregulating disulfide bond A-like protein (DsbA-L) and thus increasing adiponectin, which ultimately downregulate ICAM-1, a biomarker of endothelial dysfunction; nonetheless, its evaluation in retinal tissues is necessary [130].…”
Section: Nutraceuticalmentioning
confidence: 99%